Depression and Chronic Liver Diseases: Are There Shared Underlying Mechanisms? - Huang, Xiaoqin; Liu, Xiaoyun; Yu, Yongqiang (Frontiers in Molecular Neuroscience, 2017)
The occurrence of depression is higher in patients with chronic liver disease (CLD) than that in the general population. The mechanism described in previous studies mainly focused on inflammation and stress, which not only exists in CLD, but also emerges in common chronic diseases, leaving the specific mechanism unknown. This review was to summarize the prevalence and risk factors of depression in CLD including chronic hepatitis B (CH-B), chronic hepatitis C (CH-C), alcoholic liver disease (ALD) and non-alcoholic fatty liver disease (NAFLD), and to point out the possible underlying mechanism of this potential link. Clarifying the origins of this common comorbidity (depression and CLD) may provide more information to understand both diseases.